Media Sosial Sebagai Jembatan Pembinaan Warga Gereja Pada Masa Pandemi Covid-19 - Geptha, Hendra; Setiawan, David Eko; Revanda, Ayu Cisilia; Risno, Florensius (Sekolah Tinggi Teologi Kharisma, 2021)
Seeing the condition of the church during the pandemic era created an ironic situation for the formation of church members that was difficult to carry out. Meanwhile, the formation of church members is a very vital activity for a church. The method that the author uses is descriptive, using books, journals and research reports that can be accounted for. So that through writing this journal the writer wants to try to share an effective method of coaching church members through virtual media, so that the activities of coaching church members can continue even in a pandemic. This long distance training has become an effective solution to the restrictions imposed by the government on every place of worship in Indonesia.Melihat kondisi gereja pada masa pandemi menimbulkan suatu keadaan ironi bagi pembinaan warga gereja yang sulit dilaksanakan. Sedangkan pembinaan warga gereja sendiri adalah sesuatu kegiatan yang sangat vital bagi sebuah gereja. Metode yang penulis gunakan adalah deskriptif, menggunakan buku, jurnal dan laporan penelitan yang dapat dipertaanggungjawabkan. Sehingga melalui penulisan jurnal ini penulis ingin mencoba membagikan suatu metode pembinaan warga gereja yang efektif melalui media virtual, supaya kegiatan pembinaan warga gereja terus dapat berlangsung meskipun dalam keadaan pandemi. Pembinaan jarak jauh ini telah menjadi solusi efektif dari pembatasan-pembatasan yang diberikan pemerintah bagi setiap tempat peribadatan di Indonesia.